Climatic changes in Finland during the last hundred years - Raino Heino (Fennia: International Journal of Geography, 1978)
The account is based on the longest continuous series of meteorological records in Finland, that for the city of Helsinki, possessing temperature data from 1828 onwards and precipitation figures from 1844. The worldwide increase in temperatures from the 19th century up until the middle of the present century and the subsequent drop are clearly in evidence in Finland. An increase of 1.5 °C is to be seen in the mean annual temperature, while the changes in winter temperatures are more pronounced, especially as far as the northern parts of the country are concerned. The low winter temperatures of the period 1966–1970 and the higher winter temperatures in 1971–1975 represent the largest such fluctuations in the country’s climatic history. The outstanding feature in the long-term trends in precipitation at Helsinki is the steady increase at all seasons up to the beginning of the 20th century, after which the figures generally declined. The precipitation figures for other meteorological stations, however, include extremely variable trends. A comparison of the period 1961–1975 with the normal period 1931–1960 suggests that the summer and winter peaks have both shifted distinctly earlier, while the annual temperature range has declined.